2006
DOI: 10.5254/1.3547961
|View full text |Cite
|
Sign up to set email alerts
|

New Concept of Co-Agents for Scorch Delay and Property Improvement in Peroxide Vulcanization

Abstract: Peroxide cure is an important and widely used cure system for rubber. Several properties obtained via peroxide vulcanization are superior and not achievable with sulfur vulcanization, e.g.: aging resistance, no reversion and low compression set. However, other properties such as tensile strength and dynamic properties, are inferior to those of sulfur vulcanizates. The use of co-agents in peroxide cure leads to a certain extent to improvement in mechanical properties such as tensile strength. Nevertheless the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…Typically, at high curing temperatures, TESPT would release sulfur that is capable of increasing the cure efficiency in sulfur vulcanization system . In this work where peroxide is used as a curing agent, the formation of crosslinks through the free radicals might be obstructed by the released sulfur from TESPT, giving rise to a decrease in cure efficiency with increasing TESPT content . In addition, the crosslink density results measured via equilibrium swelling technique are presented in Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Typically, at high curing temperatures, TESPT would release sulfur that is capable of increasing the cure efficiency in sulfur vulcanization system . In this work where peroxide is used as a curing agent, the formation of crosslinks through the free radicals might be obstructed by the released sulfur from TESPT, giving rise to a decrease in cure efficiency with increasing TESPT content . In addition, the crosslink density results measured via equilibrium swelling technique are presented in Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The result may be explained by the reduced crosslink density as a consequence of the consumption of peroxy radicals in the presence of TESPT as mentioned earlier. It has been reported that every mole of the elemental sulfur would destroy about 1 mole of peroxide . Although the increase of TESPT content results in the reduced crosslink density and modulus, other mechanical properties such as tensile strength, elongation at break and tear strength are improved.…”
Section: Resultsmentioning
confidence: 99%
“…A morfologia é definida durante a vulcanização dinâmica e depende, entre outros fatores, do sistema de cura que, além do agente principal, pode envolver coagentes [1,23,24] . Grimma et al [25] ao reticular borracha EPDM da forma convencional, com peróxido de dicumila (DCP) combinado com enxofre ou agentes doadores de enxofre, como o 2-mercapto benzotiazol (MBT), obtiveram uma borracha termofixa com alto módulo e alta resistência à ruptura. Observaram, no entanto, que um dos inconvenientes para este sistema, é uma redução na resistência ao envelhecimento da borracha em temperaturas elevadas [26] , atribuída as pontes sulfídicas.…”
Section: Methodsunclassified
“…Só o aumento significativo do DCP combinado com o aumento no teor de BMI, TPV DB 3.4_1.1 resultou em um material com bom desempenho mecânico, apresentando uma tensão de ruptura de 11,4 MPa e alongamento de 175%. Estes resultados estão em concordância com os publicados por Grimma et al [25] , onde o mesmo abordou a importância do enxofre e BMI na reticulação da borracha termofixa de EPDM com peróxido de dicumila. tamanho dos domínios da fase elastomérica dispersa na matriz plástica, melhor é o desempenho mecânico do TPV.…”
Section: Deformação Permanente a Compressão -Dpcunclassified
“…In some cases, coagents are the alternatives applied to improve the crosslinking3 in thermoset rubbers manufacturing, for which sulfur is an adequate choice because of its low cost. With respect to physical mechanical properties, it was observed that the use of sulfur or the sulfur donor agent MBT (2‐mercaptobenzothiazole) as a coagent for dicumyl peroxide (DCP) contributes to the curing process, resulting in TPVs with high modulus and tensile strength but with less resistance to aging 8. A more recent work8 described the use of bismaleimide and sulfur or a sulfur donor as coagents of dicumyl peroxide in the crosslinking of EPM rubber.…”
Section: Introductionmentioning
confidence: 99%